Retinoic acid-mediated anti-inflammatory responses in equine immune cells stimulated by LPS and allogeneic mesenchymal stem cells. (October 2017) - Abdelhamid, Leila; Hussein, Hayam; Ghanem, Mostafa; Eissa, Nour
Abstract: Retinoic acid (RA), an active metabolite of vitamin A, has shown potential therapeutic immunomodulatory properties. Allogeneic mesenchymal stem cells (MSCs)-based therapy is an effective approach to induce tissue healing and regeneration in many equine orthopedic conditions. However, MSCs-based therapies induced inflammatory responses in vivo . This study aimed to: 1. Determine the effect of RA cell culture treatment on inflammatory responses of lipopolysaccharides (LPS)- and allogeneic MSCs-stimulated peripheral blood mononuclear cells (PBMCs). 2. Determine the effect of RA on stimulated MSCs viability and morphology. Allogeneic MSCs-stimulated PBMCs had significant decreases in the anti-inflammatory cytokines (IL-10, IL-1ra, TGF-β1), increases in the pro-inflammatory mediators (IL-1β, IL-6, TNF-α, SAA), and increases of CD14 and MHC II percent positive cells compared to LPS- and non-stimulated PBMCs. Retinoic acid treatment of LPS- and allogeneic MSCs-stimulated PBMCs counterbalanced the induced inflammatory responses. Moreover, RA significantly improved the viability and morphology of stimulated MSCs. These findings highlighted the potential complications of equine allogeneic MSCs-based therapies and the immuno-modulatory effect of RA on equine stimulated cells. In conclusion, the use of RA to ameliorate allogeneic MSCs therapy associated inflammation may offer advantages that would require further investigations. Highlights: Allogeneic MSCs elicit inflammatory response in vitro . Retinoic acid has immunomodulatory effects on LPS and allogeneic MSCs-stimulated PBMCs. Retinoic acid increased stimulated MSCs viability.